Diatom dan Paleolimnologi: Studi Komparasi Perjalanan Sejarah Danau Lac Saint-Augustine Quebeq-City, Canada dan Danau Rawa Pening Indonesia - Soeprobowati, Tri Retnaningsih; Hadisusanto, Suwarno (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2009)
Diatoms are a micro-alga dominates in the aquatic ecosystem. Their silicious cell wall able to preserve death diatoms in the sediment for long periods of time, therefore, diatoms have an important role in the paleolimnological analysis. Diatoms assemblages in the sediment layer express the water quality whenever the diatom lives. This article provides information how to apply diatom on the paleo-limnological analysis, supporting with the case study in the Lac Saint-Augustine Quebec-City Canada and Rawa Pening Lake Indonesia. Modern diatom and the water quality from spatial and temporal range are used as a calibration set. The diatoms of below layers, then, Weighted Averaging (WA) with the calibration set to reconstruct the water quality in the past. Previously, both in Canada and Indonesia, those lakes were oligotrophic and sharply change into eutrophic condition since a lot of human activities developed around the lakes (anthropogenic factors). Naturally, the maturity of lake can not avoid and the succession had been fast by eutrophication. Paleolimnological approach provides baseline data in the past to develop the appropriate lake management.